Long-term visual damage after acute methanol poisonings: Longitudinal cross-sectional study in 50 patients - Zakharov, Sergey; Pelclova, Daniela; Diblik, Pavel; Urban, Pavel; Kuthan, Pavel; Nurieva, Olga; Kotikova, Katerina; Navratil, Tomas; Komarc, Martin; Belacek, Jaromir; Seidl, Zdenek; Vaneckova, Manuela; et al. (Clinical toxicology, 2015)
CONTEXT: Visual disturbances due to the toxic effect of formic acid in acute methanol poisonings are generally transient. The subjective symptoms of visual toxicity may resolve within few weeks and fundoscopic signs of acute optic neuropathy subside within 1-2 months; therefore, the prevalence of long-term visual sequelae in the population of survivors of poisonings may be underestimated. OBJECTIVE: To study the prevalence and character of long-term visual sequelae of acute methanol poisonings based on the data from the Czech mass methanol outbreak in 2012. PATIENTS AND METHODS: A total of 50 patients with confirmed methanol poisoning were included in this longitudinal cross-sectional study, median age: 48 (range, 23-73) years. The following tests were performed: optical coherence tomography or OCT with evaluation of the retinal nerve fibers layer (RNFL), visual evoked potentials (VEP), magnetic resonance imaging (MRI) of brain, complete ocular examination (visual acuity/field, color vision, contrast sensitivity, and fundus), neurological examinations, and biochemical tests. RESULTS: Of 50 patients, 7/50 (14%) were discharged with diagnosed visual sequelae and 6/50 (12%) were discharged with both visual and central nervous system sequelae of poisoning. On the follow-up examination, 20/50 (40%) of the patients had long-term visual sequelae, with 8% of blindness. A total of 38% of the patients had abnormal (28% borderline) findings on RNFL, and 40% had abnormal (18% borderline) VEP. Among the patients discharged without detected visual sequelae, 8/37 (22%) had abnormal RNFL and VEP. Patients with visual sequelae had brain lesions more often (70% vs. 27%, p < 0.01). MRI identified optic nerve lesions in 2/20 cases with abnormal VEP only. The groups with and without visual sequelae differed in serum methanol, ethanol, HCO3-, formate, pH, anion gap, and base deficit (all p < 0.01). Visual disturbances on admission and coma were more prevalent in the patients with visual sequelae (p < 0.05). Patients with positive serum ethanol on admission were 93% less likely to have optical axonal damage (OR: 0.07 (95% CI: 0.01-0.8); p < 0.05). No association was found between visual sequelae and type of antidote administered, mode of hemodialysis, or folate substitution. Pre-hospital administration of ethanol seemed beneficial: these patients were 90% less likely to have abnormal RNFL findings (OR: 0.10 (95% CI: 0.02-0.52); p < 0.01). CONCLUSIONS: The long-term visual sequelae were clearly underestimated on discharge, suggesting a significantly higher amount of patients with long-term sequelae than earlier reported. Thorough examinations before discharge and during follow-up will likely uncover a higher morbidity also after methanol poisonings in general.
Keywords: Cross-Sectional Studies; Methanol; lidé středního věku; lineární modely; Predictive Value of Tests; zrak; Logistic Models; prediktivní hodnota testů; diagnostické techniky oftalmologické; Treatment Outcome; Vision Disorders; Disease Outbreaks; methanol; průřezové studie; mladý dospělý; Prevalence; Male; prevalence; dospělí; Vision, Ocular; rozdělení chí kvadrát; otrava; lidé; senioři; akutní nemoc; Diagnostic Techniques, Ophthalmological; Recovery of Function; Aged; hodnocení rizik; longitudinální studie; časové faktory; Longitudinal Studies; Czech Republic; poruchy zraku; ochranné faktory; odds ratio; Linear Models; Česká republika; Risk Factors; multivariační analýza; Protective Factors; Young Adult; ženské pohlaví; Retina; Basal Ganglia; Optic Nerve; výsledek terapie; logistické modely; Poisoning; Adult; epidemický výskyt choroby; Risk Assessment; obnova funkce; mužské pohlaví; rizikové faktory; Acute Disease; bazální ganglia; Time Factors; Middle Aged; retina; Humans; Odds Ratio; Multivariate Analysis; nervus opticus; Chi-Square Distribution; Female